Memahami Karakteristik Peserta Didik Melalui Optimalisasi Pembelajaran - Sa’adah, Siti; Hamid, Asep Lukman (Addabani: Interdisciplinary Journal of Islamic Education, 2025)
Understanding learners’ characteristics is fundamental to creating an effective and inclusive learning process. This research aims to explore learners’ various cognitive, physical, emotional, social, and cultural aspects, which affect how they learn and interact. The method used is a literature study that collects information from various sources, such as books, journals, and related articles. The results show that an in-depth understanding of learners’ characteristics allows educators to design more effective teaching strategies that suit individual needs. These characteristics include learning styles, cognitive abilities, and social and emotional factors contributing to successful learning. The research also highlights the importance of creating a learning environment that supports students’ well-being and encourages the development of their academic and non-academic potential.